SPLACE: A tool to automatically SPLit, Align, and ConcatenatE genes for phylogenomic inference of several organisms - Oliveira, Renato R. M.; Vasconcelos, Santelmo; Oliveira, Guilherme (Frontiers in Bioinformatics, 2022)
The reconstruction of phylogenomic trees containing multiple genes is best achieved by using a supermatrix. The advent of NGS technologies made it easier and cheaper to obtain multiple gene information in only one sequencing run. When there are numerous genes and organisms to be used in phylogenomics analysis, it might be difficult to organize all information and manually align the gene sequences to further concatenate them. Here we present SPLACE, a tool to automatically SPLit, Align and ConcatenatE the genes of all species of interest to generate a supermatrix file, and consequently, a phylogenetic tree, while handling possible missing data. In our findings, SPLACE is the only tool that can automatically align gene sequences and also handle missing data, and it took only a few minutes to produce a supermatrix fasta file containing 83 aligned and concatenated genes from the chloroplast genomes of 270 plant species. It is an open-source tool and is publicly available at https://github.com/reinator/splace.